PEMANFAATAN SMART BOARD DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM PADA SISWA MI DENGAN METODE AUDIO-VISUAL INTERAKTIF - Ni'matul Maula; Maulida Aristiya Putri; Halimatus Sa'diyah; Givta Novitasari; Alfiana Aqila; Ika Murtisari; Mawarida Safitri; Dian Rif'iyati (STKIP Subang, 2026)
This study focuses on the use of Smart Boards in teaching Islamic Cultural History (SKI) to Madrasah Ibtidaiyah (MI) students using an interactive audio-visual approach, employing a qualitative literature review method. The issue addressed is the limited effectiveness of traditional teaching methods in engaging students and helping them understand historical concepts that are often difficult to grasp. The objective of this study is to analyze how Smart Boards can enhance student motivation and understanding during the SKI learning process. Data were obtained from books, research articles, journals, and reliable online sources related to Smart Boards and interactive learning. The results indicate that Smart Boards significantly boost student motivation by presenting material in various formats—such as text, images, animations, audio, and video—which capture attention and spark curiosity. Students become more active and confident through interactive activities like quizzes, discussions, and digital assignments. Additionally, the Smart Board helps students better understand historical events through concrete visual presentations, making it easier for them to grasp the sequence and context. Compared to traditional methods, the Smart Board offers superior visual quality, greater interactivity, and supports diverse learning styles. In conclusion, the Smart Board has proven effective in creating a more engaging SKI learning experience.